2010
DOI: 10.1002/gea.20307
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary chemical and micromorphological observations on Urartu (800–600 B.C.) ceramics, eastern Turkey

Abstract: Anatolia has long been a major pottery production center of the ancient world, dating back 7000 cal yr B.P. The Early Iron Age Urartu Kingdom (800-600 B.C.) of eastern Anatolia is known for the production of high-quality pottery, but little is known regarding firing technology and manufacture of these ceramics. Here we present a preliminary study of Urartu ceramic micromorphology and chemistry and suggest that the Urartus had good knowledge of local geology and intentionally used chemical fluxes (Pb, Rb, and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Hence, we believe that the pottery‐paste preparation was simple and did not involve added materials or granulometric separation. Here, we can point out that the CaO concentrations of the analyzed potsherds (∼12 wt%; Table ), match those from the latest research on ancient fine pottery (e.g., Grifa et al, ; Akça et al, ). This indicates a systematic use of calcareous paste, prepared either by exploiting naturally Ca‐rich clays (marls) or by tempering with calcite.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hence, we believe that the pottery‐paste preparation was simple and did not involve added materials or granulometric separation. Here, we can point out that the CaO concentrations of the analyzed potsherds (∼12 wt%; Table ), match those from the latest research on ancient fine pottery (e.g., Grifa et al, ; Akça et al, ). This indicates a systematic use of calcareous paste, prepared either by exploiting naturally Ca‐rich clays (marls) or by tempering with calcite.…”
Section: Discussionsupporting
confidence: 82%
“…(e.g., Čargo & Miše, ). Moreover, a bentonite origin of the Vis pottery is also suggested by the SEM‐observed effect of stress coatings (Figure d), which tend to indicate the usage of highly plastic clays of montmorillonite composition (Akça et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…The presence of chlorite and calcite indicated that the firing temperatures of these historical sherds were lower than those of the updraft kiln. Akça et al (2010) reported the chemical and micro-morphological observations on Urartu ceramics from 800 to 600 BC in eastern Turkey and pointed out that the raw materials in the paste of Urartu pots consisted of mica-sericite-illite and illite-smectite mixed-layer clay minerals. Those same authors indicated that the large K and Li contents in all slips relative to the bodies reveal the possible use of feldspar and/or illitic clays along with spodumene (LiAlSi 2 O 6 ) and lepidolite K(Li, Al) 2-3 (AlSi 3 O10)(O, OH,F) 2 , minerals commonly found in geological formations of the Van region (Degens et al, 1984).…”
Section: Properties Of Pottery Clays In the Lake Van Regionmentioning
confidence: 99%
“…The Urartu Kingdom (800-600 BC) was located in the highlands between Anatolia, Mesopotamia and the Caucasian mountains. Regional prehistoric and traditional ceramic examples (Kılıç & Çalısķan, 2005) and a group of Urartian and Roman ceramic pieces collected from the castle of Van (Akça et al 2010) have been analysed in a number of archaeometry projects. Sakarya et al (1990) examined 12 th and 13 th century ceramics from Samsat, in southeastern Turkey, and the same research group (Kapur et al, 1992) also examined an assemblage of Chalcolithic-early Bronze Age ceramics from Ikiztepe in Turkey.…”
mentioning
confidence: 99%